Managing creativity and innovation: The challenge for cultural entrepreneurs - Wilson, Nicholas. C.; Stokes, David (Journal of small business and enterprise development, 2005)
The purpose of this study is to distinguish managing creativity from managing innovation and highlight the importance for cultural entrepreneurs of recognizing the differences between the two. The methodology used is based on government-sponsored research project looking at access to finance in the UK music industry. Interviews were carried out with cultural entrepreneurs, finance providers and industry experts. A conceptual model of work and creative production put forward by is used as a foundation for analysis. The findings of the study highlights the importance of recognizing the differences between managing creativity and innovation, and call for effective management of them both, through developing business communication skills, external focus and promotional strategies. The different nature and role of collective activities associated with promoting creativity and innovation are highlighted.